بلوچی گیدی شاعری ءَ موتک: Elegy in Balochi Folklore - Baloch, Nasreen (Hanken, 2009)
Balochi folk poetry has been a dominant factor throughout the Baloch history. The Baloch folk poetry consists of sipat, Halo, Ladok, Lulli, Zahirok, lilo .laeladi, Dihi, and Motk (elegy). The aim of this paper is to discuss the aspects of elegy in the Baloch society during the death of a beloved one. This paper shows different verses concerning to the elegy will be focused in detail to show the richness of Baloch folk poetry in the Balochi society.